Size‐Tunable Olive‐Like Anatase TiO2 Coated with Carbon as Superior Anode for Sodium‐Ion Batteries. Issue 40 (30th August 2016) - Chen, Jun; Zhang, Yan; Zou, Guoqiang; Huang, Zhaodong; Li, Simin; Liao, Hanxiao; Wang, Jufeng; Hou, Hongshuai; Ji, Xiaobo
Abstract : Olive‐shaped anatase TiO2 with tunable sizes in nanoscale are designed employing polyvinyl alcohol (PVA) as structure directing agents to exert dramatic impacts on structure shaping and size manipulation. Notably, the introduced PVA simultaneously serves as carbon sources, bringing about a homogenous carbon layer with intimate coupling interfaces for boosted electronic conductivity. Constructed from tiny crystalline grains, the uniformly dispersed carbon‐coated TiO2 nano‐olives (TOC) possess subtle loose structure internally for prompt Na + transportations. When utilized for sodium‐ion storage, the size effects are increasingly significant at high charge–discharge rates, leading to the much superior rate performances of TOC with the smallest size. Bestowed by the improved Na + adsorption and diffusion kinetics together with the promoted electron transfer, it delivers a high specific capacity of 267 mAh g −1 at 0.1 C (33.6 mA g −1 ) and sustains 110 mAh g −1 at a rather high rate of 20 C. Even after cycled at 10 C over 1000 cycles, a considerable capacity of 125 mAh g −1 with a retention of 94.6% is still obtained, highlighting its marvelous long‐term cyclability and high‐rate capabilities. Abstract : Size‐tunable olive‐like anatase TiO2 @carbon is proposed as superior anode for Na‐ion batteries featuring remarkable high‐rate capabilities and cycling stabilities. Benefiting from promoted electron transport and shortened Na + difusion length, a high reversible capacity of 267 mAh g −1 at 0.1 C and 125 mAh g −1 at 20 C after 1000 cycles are delivered by the smallest TiO2 nano‐olives.